Experience in Studying Seroprevalence to SARS-CoV-2 Virus in the Population of the Irkutsk Region during COVID-19 Outbreak - A. Yu. Popova; E. B. Ezhlova; A. A. Mel’nikova; S. V. Balakhonov; M. V. Chesnokova; V. I. Dubrovina; L. V. Lyalina; V. S. Smirnov; A. G. Trukhina; A. N. Perezhogin; A. B. Pyatidesyatnikova; D. D. Bryukhova; et al. (Проблемы особо опасных инфекций, 2020)
Objective of the seroepidemiological study was to determine the level and structure of herd immunity to SARS-CoV-2 among the population of the Irkutsk Region during the period of an increase in the incidence of COVID-19.Materials and methods. The content of antibodies to SARS-CoV-2 was determined by ELISA applying a  reagent panel “ELISA anti-SARS-Cov-2 IgG” produced by the State Scientific Center of Applied Microbiology and Biotechnology (Obolensk).Results and discussion. The investigation has revealed that the herd immunity of the total population of Irkutsk Region amounted to 5.8 %. The greatest share of seropositive persons was among the children aged 14–17 (13.8 %) and 1–6 (11.8 %). It has been established that the risk of infection increases by 3.1 times in case of contact with COVID-19 patients. After exposure to COVID-19, antibodies were produced in 56.5 % of the cases. The share of asymptomatic forms among seropositive residents of the Irkutsk Region reached 81.2 %. Consequently, during the chosen period of increased COVID-19 incidence among the population of Irkutsk Region low level of seroprevalence was formed. A significant proportion of asymptomatic forms of infection characterize high intensity of the latently developing epidemic process. The results obtained can be used when organizing preventive measures, including vaccination, and for forecasting morbidity rates.